KONSUMSI SAYUR DAN BUAH DI MASYARAKAT DALAM KONTEKS PEMENUHAN GIZI SEIMBANG - Aswatini Raharto; Mita Noveria; NFN Fitranita (Research Centre for Population, Indonesian Institute of Sciences, 2008)
Vegetables and fruit consumption of Indonesian population increased from 70 kcal/ capita/day in 1999 to 95 kcal/capitalday in 2007. That covered only about 58% in 1999, and 79% in 2007, of 120 kcal/capitalday minimum daily requirement. Therefore some efforts are needed to increase people vegetables and fruits consumption, according to Desirable Dietary Pattern. This paper aims to explain the pattern and behaviour of vegetable and fruit consumption in Indonesia and to explore understanding on knowledge and attitudes underlying that pattern and behaviour. The effort needed to increase the vegetables and fruit consumption includes not only infrastructures development to increase availability of vegetables and fruit, but also some efforts to increase people knowledge and awareness on the importance of vegetables and fruit consumption, by conducting intensive socialization and promotion. Analysis in this paper is based on secondary macro data from National Social Economic Survey (Susenas) and also primary (micro) data collected during a series of case studies conducted in Lampung and East Nusa Tenggara (N'IT) provinces, in 2003 to 2006 and further in depth study in 2008.Keyword: Vegetable, fruit, consumption, balanced dietary intake, knowledge and practice.